Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5539/ijps.v8n4p16
|View full text |Cite
|
Sign up to set email alerts
|

Early Nurturing Experiences, Self-Compassion, Hyperarousal and Scleroderma The Way We Relate to Ourselves May Determine Disease Progression

Abstract: Scleroderma is a rare, painful and complex autoimmune connective tissue disease that can lead to death. The physiology of symptom onset and progression and the psychological aspects of living with this chronic disease have been studied fairly extensively. However, there is limited knowledge about scleroderma and negative physiological arousal (hyper-arousal: linked to immune dysfunction resulting in autoimmunity in the face of stressful events) and how levels of hyper-arousal are related to stress experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, Pace and colleagues found that people who engaged in higher levels of compassion focused meditation scored lower on physiological immune related stress responses such as cortisol levels and on psychological measures of distress; suggesting that stress induced immune and behavioural responses may be moderated by compassion focused meditations (Pace et al, 2009). A study on an autoimmune disease (scleroderma) and self-compassion found that lower levels of hyper-arousal (a response that can negatively impact on the immune system) were related to greater levels of self-compassion and a later onset of disease (Kearney & Hicks, 2016). In the study by Wren et al (2011), the effects of selfcompassion lead to better management of persistent musculoskeletal pain.…”
Section: Self-compassion Benefits: Biopsychosocial Implicationsmentioning
confidence: 99%
“…For example, Pace and colleagues found that people who engaged in higher levels of compassion focused meditation scored lower on physiological immune related stress responses such as cortisol levels and on psychological measures of distress; suggesting that stress induced immune and behavioural responses may be moderated by compassion focused meditations (Pace et al, 2009). A study on an autoimmune disease (scleroderma) and self-compassion found that lower levels of hyper-arousal (a response that can negatively impact on the immune system) were related to greater levels of self-compassion and a later onset of disease (Kearney & Hicks, 2016). In the study by Wren et al (2011), the effects of selfcompassion lead to better management of persistent musculoskeletal pain.…”
Section: Self-compassion Benefits: Biopsychosocial Implicationsmentioning
confidence: 99%